May Measurement Month 2018: an analysis of blood pressure screening campaign results in India. (28th August 2020) - Maheshwari, Anuj; Verma, Narsingh; Bhardwaj, Shipra; Jose, Arun P; Bhalla, Sandeep; More, Arun; Patil, Mansi; Gupta, Amit; Gupta, Bal Kishen; Takalkar, Anant; Gupta, Priyanka; Pandey, Nikki; et al.
Abstract: Hypertension (HTN) is the greatest attributable risk factor for cardiovascular disease in India. Recent studies have reported the crude prevalence of HTN in India to be 25.3%. In the May Measurement Month (MMM) screening campaign of 2017 conducted in India, 31.8% had HTN. In order to ratify earlier results, and further understand the awareness and control levels of HTN in India, organizations that participated in MMM 2017 decided to participate in the MMM global screening initiative of the International Society of Hypertension for a 2nd consecutive year. A total of 345 234 individuals were screened in MMM 2018. There were more than 1000 screening locations that included hospitals, clinics, workplaces, and special health camps organized across the country. After applying multiple imputation, a total of 111 462 (32.3%) individuals had HTN of whom 63 415 (55.6%) were aware of HTN and 61 646 (55.3%) were on antihypertensive medicines, out of which 15 583 (25.3%) were uncontrolled. Overall 57 864 (41.3%) hypertensives were uncontrolled. About half (44.7%) of hypertensive population in India were not on treatment. Around two-thirds (65.7%, n  = 226 924) had not measured their blood pressure (BP) in last 12 months and 64% measured their BP for the first time in their life during the campaign, which strongly indicates the need for large scale awareness drives. This study suggests that opportunistic periodic public health screening at a national level is needed to increase HTN detection, treatment, control, and countrywide awareness in highly populated nations like India.